Penguatan Partisipasi Publik melalui E-Demokrasi: Studi Kasus Tata Kelola Digital melalui Aplikasi PADUKO di Kota Padang Panjang - Dewi Dahlan (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2025)
The rapid development of information and communication technology has expanded opportunities for governments to promote participatory, transparent, and accountable governance through e-democracy. This study analyzes the implementation of the PADUKO (Online Population Administration Services) application as a form of digital governance and e-democracy in Padang Panjang City. Using an evaluative case study with a qualitative approach, data were collected through in-depth interviews, observation, and document analysis, and were validated using source triangulation and focus group discussions. The findings show that PADUKO improves service transparency, access to digital information, citizen participation, and inter-agency collaboration in population administration services. However, citizen participation remains largely procedural and consultative, corresponding to the levels of consultation and placation in Arnstein’s ladder of participation. Challenges such as unequal digital literacy, limited infrastructure, and uneven public awareness continue to constrain meaningful engagement. This study concludes that the effectiveness of e-democracy initiatives depends not only on technological readiness but also on supportive institutional frameworks and active community involvement to achieve substantive citizen empowerment in local governance.